2003
DOI: 10.1017/s0272263103000019
|View full text |Cite
|
Sign up to set email alerts
|

NEGATIVE FEEDBACK AND POSITIVE EVIDENCE IN TASK-BASED INTERACTION

Abstract: This study examines the role of task-based conversation in second language (L2) grammatical development, focusing on the short-term effects of both negative feedback and positive evidence on the acquisition of two Japanese structures. The data are drawn from 55 L2 learners of Japanese at a beginning level of proficiency in an Australian tertiary institution. Five different types of interactional moves made by native speaker interlocutors during task-based interaction were identified, by way of which learners r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(153 citation statements)
references
References 57 publications
2
149
1
1
Order By: Relevance
“…Table 1 below summarises key findings from the research reviewed above on focus on form. Lightbown and Spada (1990), Doughty and Varela (1998), Harley (1998), Muranoi (2000), Ellis (2002), Mennim (2003), Lyster (2004), Loewen (2005), Bouffard and Sarkar (2008) Use of focuson-form instruction in CLT classrooms Focus on form may occur without interfering with the communicative flow of the lessons Seedhouse (1997), Doughty and Varela (1998), Ellis et al (2001aEllis et al ( 2001b Effectiveness of focus-onform instruction depending on type Using both explicit and implicit focus-on-form strategies can promote language learning Spada (1997) Using implicit eliciting focus on form can promote language learning Lyster (2004) and Loewen (2004) Using explicit focus-on-form strategies can promote language learning Ellis (2002) and Fuente (2006) Research on learners Learners believe that they can attend to form and meaning at the same time Doughty and Varela (1998) Learner-driven independent focus on form (learner noticing) seems to have positive impact on their L2 proficiency Mackey (2006), Mennim, (2007, Hanaoka (2007) When learners initiate focus on form they seem to address lexical aspects in particular Williams (1999), Ellis et al (2001a) More proficient learners are likely to pay more attention to form than less proficient learners Williams (1999) Research on teachers Discrepancies in teacher beliefs and practice in relation to their use of focus on form in communicatively oriented classrooms Basturkmen et al (2004) TeachersÕ experience seems to play a role in teachersÕ use of focus on form Mackey, et al (2004) Corrective feedback Iwashita (2003: 2) defines corrective feedback as Ôsome kind of native speaker response to what the learner has saidÕ; it may in fact be better understood as some kind of response from a more expert language user, often a teac...…”
Section: Focus-on-form Instruction: Research On Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 below summarises key findings from the research reviewed above on focus on form. Lightbown and Spada (1990), Doughty and Varela (1998), Harley (1998), Muranoi (2000), Ellis (2002), Mennim (2003), Lyster (2004), Loewen (2005), Bouffard and Sarkar (2008) Use of focuson-form instruction in CLT classrooms Focus on form may occur without interfering with the communicative flow of the lessons Seedhouse (1997), Doughty and Varela (1998), Ellis et al (2001aEllis et al ( 2001b Effectiveness of focus-onform instruction depending on type Using both explicit and implicit focus-on-form strategies can promote language learning Spada (1997) Using implicit eliciting focus on form can promote language learning Lyster (2004) and Loewen (2004) Using explicit focus-on-form strategies can promote language learning Ellis (2002) and Fuente (2006) Research on learners Learners believe that they can attend to form and meaning at the same time Doughty and Varela (1998) Learner-driven independent focus on form (learner noticing) seems to have positive impact on their L2 proficiency Mackey (2006), Mennim, (2007, Hanaoka (2007) When learners initiate focus on form they seem to address lexical aspects in particular Williams (1999), Ellis et al (2001a) More proficient learners are likely to pay more attention to form than less proficient learners Williams (1999) Research on teachers Discrepancies in teacher beliefs and practice in relation to their use of focus on form in communicatively oriented classrooms Basturkmen et al (2004) TeachersÕ experience seems to play a role in teachersÕ use of focus on form Mackey, et al (2004) Corrective feedback Iwashita (2003: 2) defines corrective feedback as Ôsome kind of native speaker response to what the learner has saidÕ; it may in fact be better understood as some kind of response from a more expert language user, often a teac...…”
Section: Focus-on-form Instruction: Research On Learnersmentioning
confidence: 99%
“…Table 2 below summarises the key findings from the research on corrective feedback. Corrective, or negative, feedback seems to be capable of facilitating L2 development Long (1996), Iwashita (2003), McDonough (2005) …”
Section: Corrective Feedback: Learner Pair-correctionmentioning
confidence: 99%
“…In addition, many studies compare the effects of different types of CF received by learners (e.g., Ellis, Loewen, & Erlam, 2006;Panova & Lyster, 2002;Iwashita, 2003;Philp, 2003). Some studies suggest that learners could benefit more from explicit rather than implicit CF (e.g., Carroll & Swain, 1993;Ellis, Loewen, & Erlam, 2006;Kim & Mathes, 2001;Varnosfadrani & Basturkmen, 2009).…”
Section: Previous Studiesmentioning
confidence: 99%
“…Yang & Lyster (2010) explore the effects of form-focused practice and feedback on acquisition of English regular and irregular past tense forms and found that prompts were effective in increasing accuracy. Iwashita (2003) examines the role of task-based interaction in Japanese L2 grammatical development. She concluded that implicit negative feedback had a beneficial effect on the short-term development of target grammatical structures but recasts had a larger impact.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Errors play a crucial role in the learning process. The errors a learner makes can be considered as a crucial source of information about the nature of his/her knowledge (Edge, 1989;Iwashita, 2003). From the analysis of the learner's errors, teachers are able to infer the nature of learners' knowledge at that point in their learning and understand what they still have to learn (Abbasi & Karimnia, 2011).…”
Section: Introductionmentioning
confidence: 99%